2021
DOI: 10.1063/5.0041369
|View full text |Cite
|
Sign up to set email alerts
|

Biaxial atomically resolved force microscopy based on a qPlus sensor operated simultaneously in the first flexural and length extensional modes

Abstract: Frequency-modulation atomic force microscopy (AFM) with a qPlus sensor allows one to atomically resolve surfaces in a variety of environments ranging from low-temperature in ultra-high vacuum to ambient and liquid conditions. Typically, the tip is driven to oscillate vertically, giving a measure of the vertical force component. However, for many systems, the lateral force component provides valuable information about the sample. Measuring lateral and vertical force components simultaneously by oscillating vert… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…However, although the combination of in‐plane and out‐of‐plane oscillation modes is feasible, the implementation is not straightforward because qPlus sensors require some nonstandard AFM equipment. [ 15–17 ] Another option for achieving ultrasmall oscillation amplitudes is to exploit higher flexural cantilever eigenmodes because they are stiffer than the fundamental eigenmode. Atomic resolution has been shown successfully on different substrates in air when higher eigenmodes were used for the amplitude or frequency‐shift feedback.…”
Section: Introductionmentioning
confidence: 99%
“…However, although the combination of in‐plane and out‐of‐plane oscillation modes is feasible, the implementation is not straightforward because qPlus sensors require some nonstandard AFM equipment. [ 15–17 ] Another option for achieving ultrasmall oscillation amplitudes is to exploit higher flexural cantilever eigenmodes because they are stiffer than the fundamental eigenmode. Atomic resolution has been shown successfully on different substrates in air when higher eigenmodes were used for the amplitude or frequency‐shift feedback.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently demonstrated that both LFM and AFM are possible with a qPlus sensor by using the length-extension and first flexural modes at room temperature. 37) Yamada et al have also proposed implementing simultaneous LFM measurements with a longer tip that will oscillate laterally at the second flexural mode. 38) LFM is an exciting technique that is relatively straightforward to implement in any existing qPlus-based system.…”
Section: Discussionmentioning
confidence: 99%
“…Line 4: Tuning fork sensor [13] operated in its flexural mode for comparison with lines 1-3. Line 5: For bi-axial force gradient measurements with a tuning fork [65], its length extension mode was used to map the vertical force gradient. Line 6: The cantilever with the properties given in line 3 now compared to the sensitivity of the tuning fork length extension mode given in line 5.…”
Section: Force Gradient Noise and Measurement Bandwidthsmentioning
confidence: 99%